TERIFLUNOMIDE IN EARLY STAGE MS: RESULTS FROM TOPIC. Issue 10 (9th September 2014) - Turner, Benjamin; Bauer, Deborah; Benamor, Myriam; Truffinet, Philippe; Miller, Aaron
Abstract : Introduction: Teriflunomide is a once-daily oral immunomodulator approved for relapsing–remitting multiple sclerosis (RRMS). Here we report the efficacy and safety outcomes from the TOPIC trial (NCT00622700 ). Methods: TOPIC was a double-blind, placebo-controlled, parallel-group study in patients with a first clinical episode consistent with MS. Patients were randomised to teriflunomide 14 mg, 7 mg or placebo. The primary endpoint was occurrence of a new clinical relapse, and the key secondary endpoint was occurrence of a new clinical relapse or MRI lesion. Safety and tolerability were also assessed. Results: Baseline characteristics were generally well balanced across groups. Teriflunomide 14mg significantly reduced the risk of a new clinical relapse by 42.6% (p=0.0087) and the risk of a new clinical relapse or MRI lesion by 34.9% (p=0.0003) versus placebo. Teriflunomide 14 mg significantly reduced total lesion volume increase from baseline at every time point and the number of gadolinium-enhancing T1 lesions per scan versus placebo. Safety observations were similar to those of TEMSO and TOWER. Conclusions: Teriflunomide demonstrated efficacy in patients with early stage MS. Together with outcomes from TEMSO and TOWER, these findings support the beneficial effect of teriflunomide across a broad range of patients and disease activity.